Syntax : a generative introduction - Carnie, Andrew, 1969- ([Hoboken, New Jersey] : Wiley-Blackwell, 2013)
"Andrew Carnie's bestselling textbook on syntax has guided thousands of students through the discipline of theoretical syntax; retaining its popularity due to its combination of straightforward language, comprehensive coverage, and numerous exercises. In this third edition, topics have been updated, new exercises added, and the online resources have been expanded. Supported by expanded online student and instructor resources at www.wiley.com/go/carnie, including extra chapters on HPSG, LFG and time-saving materials for lecturers, including problem sets, PowerPoint slides, and an instructors' manual Features new chapters on ellipsis, auxiliaries, and non-configurational languages Covers topics including phrase structure, the lexicon, Case theory, movement, covert movement, locality conditions, VP shells, and control Accompanied by a new optional workbook, available separately, of sample problem sets which are designed to give students greater experience of analyzing syntactic structure "--
"Andrew Carnie's bestselling textbook on syntax has guided thousands of students through the discipline of theoretical syntax; retaining its popularity due to its combination of straightforward language, comprehensive coverage, and numerous exercises. In this third edition, topics have been updated, new exercises added, and the online resources have been expanded"--
Includes bibliographical references (pages 511-518) and index.
Keywords: Grammar, Comparative and general -- Syntax; Generative grammar; LANGUAGE ARTS & DISCIPLINES / Linguistics / Syntax